Personalized Independent Learning Systems in High Technology Environments - Squire, Kurt.; Johnson, Christine; Bichelmeyer, Barbara ([Washington D.C.] : Distributed by ERIC Clearinghouse, 1998)
In order to be effective, instruction must be more than tailored to the individual: it must be a part of a larger system designed to support individualized learning. An effective individualized instructional environment is a dynamic system; it involves instructors who embrace the concept of individualizing instruction, and provides guidance to students throughout their educational lives, attending to their personal needs. In a Personalized Independent Learning System (PILS), the learning experiences are personalized in two ways: the content chosen reflects an individual's needs, and the learning process reflects an individual's needs. Independence is encouraged in PILS by focusing on producing autonomous, self-regulated learners. Emphasis is placed on developing learners' metacognitive and critical thinking skills and ability to function as experts within their domain. A PILS environment is characterized by learning outcomes rather than the instructional materials involved, and it approaches education systematically. Networked computer technologies such as teleconferencing, the World Wide Web, and e-mail can provide valuable support to PILS. (Contains 17 references.) (AEF)
ERIC Note: In: Proceedings of Selected Research and Development Presentations at the National Convention of the Association for Educational Communications and Technology (AECT) Sponsored by the Research and Theory Division (20th, St. Louis, MO, February 18-22, 1998); see IR 019 040.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Computer Assisted Instruction; Educational Environment; Educational Philosophy; Electronic Mail; Independent Study; Individualized Instruction; Instructional Design; Instructional Effectiveness; Learner Controlled Instruction; Lifelong Learning; Models; Student Needs; Technology Integration; Teleconferencing; Thinking Skills; World Wide Web; Reports, Evaluative; Speeches/Meeting Papers